Factors Associated with Cardiorespiratory Fitness in Breast Cancer Survivors from the State of Santa Catarina, Brazil: Cross-Sectional Study - Leonessa Boing; João Antonio Gesser Raimundo; Gustavo Soares Pereira; Melissa de Carvalho Souza Vieira; Juliana da Silveira; Patrícia Severo dos Santos Saraiva; Danielly Yani Fausto; Julia Beatriz Bocchi Martins; Adriana Coutinho de Azevedo Guimarães; Alice Erwig Leitão; Tatiana de Bem Fretta; Brigid M. Lynch (Revista Brasileira de Cancerologia, 2023)
Introduction: Oxygen consumption (VO2) is indicative of cardiorespiratory fitness (CRF) and lower levels are related to a higher risk of total mortality among individuals with cancer whose therapy can have adverse consequences on the cardiovascular system. Objective: To examine the associations of patient-reported sociodemographic, clinical, anthropometric outcomes and functional variables with CRF in 69 women (55±10 years) and to identify whether walking is a predictor of peak VO2 variation in this population with breast cancer (BC). Method: Female BC survivors receiving hormone therapy after two types of surgery (breast-conserving and mastectomy) underwent a CRF test on a cycle ergometer to measure peak VO2. A questionnaire containing sociodemographic, clinical data, patient reported outcomes (PROs) (depressive symptoms, sleep quality, fatigue, body image) and self-reported walking and tests to measure body fat percentage, waist circumference, flexibility and shoulder range of motion (RoM) were performed. Results: Unemployment and retirement were associated with low CRF, as was the use of aromatase inhibitors instead of tamoxifen. Depressive symptoms, worse body image, greater waist circumference, less flexibility and shoulder RoM were also associated with low CRF. Walking duration, controlled for age and body mass index (BMI), is a 13% predictor of peak VO2 variance in this sample. Conclusion: These factors must be considered in understanding the CRF profile of BC survivors. As walking was a predictor of peak VO2 variance, it should be recommended as a type of physical activity for patients with BC using hormone therapy.